Prevalence and trends of diarrhoea in children under five in Masiphumelele, Cape Town, South Africa (2019-2023) - Mokoena, Prince (Department of Public Health and Family Medicine, 2025)
Background: Diarrhoea in children under five years is a major cause of morbidity and mortality in SubSaharan Africa. Informal settlements are disproportionately affected due to overcrowding, inadequate sanitation, and unsafe water practices. This study provides a comprehensive analysis of diarrhoea prevalence, demographic distribution, seasonal patterns, and the effect of the COVID-19 pandemic on paediatric diarrhoea cases in Masiphumelele Township, Cape Town, South Africa (2019-2023). Method: A retrospective observational analysis of clinical records from January 2019 to December 2023 at Masiphumelele Clinic was conducted. The prevalence of diarrhoea was calculated using various denominators, including the total clinic patients, the total children under five years of age, and the total number of clinic patients with diarrhoea. Statistical analyses evaluated trends using proportion comparisons (Z-tests) and temporal patterns (Chi-squared tests for trends) evaluate significant changes in prevalence over time and during the COVID19 period. Results: Diarrhoea in children under five years of age accounted for 2.04% of the total 391355 clinic visits, with the trend rising from 79 cases in 2019 to 233 in 2023. Children under five years of age accounted for 11.2% of all clinic patients and 74.7% of cases of diarrhoea. The highest burden was observed among boys (56%) and children between 2 and 3 years (28.2%). Seasonal peaks in diarrhoea prevalence were observed in the warmer months, with the highest case counts recorded in February (11.7%) and November (10.2%), which is consistent with the known diarrhoeal disease seasonality in South Africa. The prevalence of diarrhoea increased significantly from 1.37 cases per 1000 before the COVID-19 pandemic to 2.51 cases per 1000 after the pandemic (p < 0.001). This increase may reflect healthcare disruptions, limited access to prevention services, and changes in hygiene practices during the pandemic. Conclusions: This study highlights the continued burden of diarrhoeal diseases on informal settlements and the worsening role of the COVID-19 pandemic. Targeted interventions that focus on improving water and sanitation infrastructure, seasonal preparation, and educational campaigns that focus on age-specific vulnerabilities are essential. Strengthening public health policies and health systems that address seasonal disease patterns and vulnerabilities is critical to mitigate the effects of diarrhoea and ensure resilience to future public health crises.